Assessment of nylon versus polyester ropes for mooring of floating wind turbines. (15th June 2023) - Sørum, Stian H.; Fonseca, Nuno; Kent, Michael; Faria, Rui Pedro
Abstract: With the development of floating wind turbines comes the need for mooring systems suitable for shallow water depths. Compliance becomes challenging for mooring systems composed of chain and wire rope. Polyester ropes can improve compliance, but the even lower stiffness of nylon may further reduce mooring line loads. However, fatigue lifetime of nylon ropes has been limiting. This paper presents results of stiffness and fatigue tests on long lay polyester and nylon ropes and evaluates the performance of two mooring systems for a floating wind turbine. The fibre ropes' complex stiffness behaviour is modelled by the Syrope model, with mooring analyses based on fully coupled time-domain simulations. Nylon ropes reduce the dynamic loads in the mooring system, particularly wave frequency loads. This improves the fatigue lifetime of all components, allowing a reduction of the chain cross-section area by ∼ 40% compared to the polyester-based mooring system. The long lay nylon ropes show excellent fatigue properties. With the reduced loading, the lifetime is longer for the nylon ropes than the polyester ropes. Ultimate loads are also reduced when using nylon, allowing reduction of the breaking load by ∼ 30%. This gives a thinner and lighter rope than the equivalent polyester rope. Highlights: Stiffness, break load and fatigue testing of long lay nylon and polyester ropes. Mooring analysis of floating wind turbine with nylon and polyester ropes. Extreme loads and fatigue damage reduces with nylon mooring lines. Nylon ropes open for more flexible mooring system designs.